HIV reservoir: antiviral immune responses and immune interventions for curing HIV infection. Issue 22 (20th November 2022) - Li, Shuang; Moog, Christiane; Zhang, Tong; Su, Bin
Abstract : Abstract: Antiretroviral therapy against human immunodeficiency virus (HIV) is effective in controlling viral replication but cannot completely eliminate HIV due to the persistence of the HIV reservoir. Innate and adaptive immune responses have been proposed to contribute to preventing HIV acquisition, controlling HIV replication and eliminating HIV-infected cells. However, the immune responses naturally induced in HIV-infected individuals rarely eradicate HIV infection, which may be caused by immune escape, an inadequate magnitude and breadth of immune responses, and immune exhaustion. Optimizing these immune responses may solve the problems of epitope escape and insufficient sustained memory responses. Moreover, immune interventions aimed at improving host immune response can reduce HIV reservoirs, which have become one focus in the development of innovative strategies to eliminate HIV reservoirs. In this review, we focus on the immune response against HIV and how antiviral immune responses affect HIV reservoirs. We also discuss the development of innovative strategies aiming to eliminate HIV reservoirs and promoting functional cure of HIV infection.